แนวทางการพัฒนาวัฒนธรรมความปลอดภัยของหน่วยบินสังกัดกระทรวงกลาโหม - กุดแถลง เปรมินทร์; นามแสง อภิรดา; คำเพราะ ธัญญรัตน์ (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2021)
This independent research is a qualitative study. The purposes of this research are to study and compare the safety culture differences between Safety Management Manual (Doc9859) 4th Edition (2018) of the International Civil Aviation Organization and aviation safety regulation of the Ministry of Defence in order to present guidelines for the development of aviation safety culture under flying units in the Ministry of Defence. The study found that the safety culture according to Safety Management Manual (Doc9859) 4th Edition (2018) of the International Civil Aviation Organization and the aviation safety regulation of the Ministry of Defence are different in 5 areas; 1) Adaptability 2) Awareness 3) Behaviour with respect to safety 4) Actions related to information and 5) Trust. To promote more efficiency in the safety culture of the flying units under the Ministry of Defence, the flying units under the Ministry of Defence should do the following; 1) Increasing the improvement of monitoring and reporting in practice after receiving safety recommendations 2) Increase surveillance obligations in random form 3) To conduct investigations and analyzes to find the cause of the real nature of the event or thing that may cause harm 4) Setting the time for Foreign Object Debris (FOD) detection 5) Increasing measures to prevent damage from external foreign bodies, especially preventive and assessment measures 6) Setting the criteria for consideration to reward aviation safety for dedication and being creative in the work award 7) Penalties are not given against the reporter regarding the reporting of safety issues 8) Increasing the efficient in promoting communication and dissemination of safety information both inside and outside the organization 9) Requiring the training in the subjects related to the knowledge transfer of the previous safety topics to pilots or people involved in flight missions 10) Increasing the safety related meeting with external agencies 11) Making the report of an incident or potential hazard as a confidential report, but with the name of the reporter and 12) Carrying out the safety awards.